Highly Sensitive Determination of Atropine in Pharmaceuticals, Biological Fluids and Beverage on Planar Electrochemical Cell with Working Boron-Doped Diamond Electrode. (10th November 2022) - Dushna, Olha; Dubenska, Liliya; Vojs, Marian; Marton, Marián; Patsay, Igor; Ivakh, Sophia; Plotycya, Serhiy
Highlights: The miniature planar electrochemical cell with BDDE for sensitive determination of alkaloid atropine. Excellent sensitivity, lower limit of detection, superior reproducibility, selectivity and useful for routine pharmaceutical analysis. Some novel validated methods for atropine determination in drugs, biological fluids and commercial beverages without multistage dilution and separation. One drop of the beverage is enough for Cola analysis for atropine content. Abstract: In the present paper, for the first time, a planar electrochemical cell formed of a novel screen-printed sensor with the working boron-doped diamond electrode (BDDE) was used for the voltammetric determination of alkaloid atropine (ATR). Different BDDE diameters of 1, 2 and 3 mm were used. ATR gives one irreversible oxidation peak at the potential of 1.5 V in the presence of 2 M HClO4 . Two irreversible peaks of ATR oxidation at potentials 1.0 V and 1.2 V were obtained using Britton-Robinson buffer at pH 11. Differential pulse voltammetry (DPV) and square-wave voltammetry (SWV) were used to obtain calibration curves for ATR on BDDE. The use of cells with various BDDE diameters enables an expansion of the range of linear concentration. The limit of detection (LOD) reaches the lowest value of 0.08 μМ using DPV on BDDE with the diameter of 3 mm. Using the working electrode with the diameter of 1 mm it is possible to determine 4.1 μМ ATR. ATR can be determined in drugs (without multistage dilution and separation) and biological fluids using planar cells. The method has also been approved to determine ATR at the lethal dose level and below in Cola. One drop of the beverage is enough for this analysis. The developed methods were validated according to the criteria such as linearity, limits of detection and quantification, accuracy, precision, stability, and selectivity. The presented analysis protocols are rapid, inexpensive, portable, and relevant. Graphical abstract: Image, graphical abstract